2015
DOI: 10.1172/jci80319
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal CGHC motif of protein disulfide isomerase supports thrombosis

Abstract: Protein disulfide isomerase (PDI) has two distinct CGHC redox-active sites; however, the contribution of these sites during different physiologic reactions, including thrombosis, is unknown. Here, we evaluated the role of PDI and redox-active sites of PDI in thrombosis by generating mice with blood cells and vessel wall cells lacking PDI (Mx1-Cre Pdifl/fl mice) and transgenic mice harboring PDI that lacks a functional C-terminal CGHC motif [PDI(ss-oo) mice]. Both mouse models showed decreased fibrin deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
142
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(153 citation statements)
references
References 60 publications
10
142
1
Order By: Relevance
“…PACMA31 has an optimal fit with the second catalytic domain of PDI, 54,55 and this PDI domain has recently been shown to be crucial for regulating platelet activation and thrombosis in vivo. 31,56 Under the experimental conditions, addition of the PDI inhibitor PACMA31 produced significant and similar inhibition of these platelet activation parameters in WT and C5-deficient plasma ( Figure 2D-F and supplemental Figure 2C), indicating that C5 activation is not connected to PDI roles in platelet activation. Importantly, PACMA31 added to C3 2/2 plasma also further suppressed convulxin-induced VWF binding, integrin a IIb b 3 activation, and P-selectin exposure, but showed no significant additive inhibition of the reduced platelet surface PS exposure seen in C3 2/2 mice (Figure 2A-C and supplemental Figure 2A).…”
Section: C5 Specifically Contributes To Fibrin Formation In Venous Thmentioning
confidence: 83%
See 1 more Smart Citation
“…PACMA31 has an optimal fit with the second catalytic domain of PDI, 54,55 and this PDI domain has recently been shown to be crucial for regulating platelet activation and thrombosis in vivo. 31,56 Under the experimental conditions, addition of the PDI inhibitor PACMA31 produced significant and similar inhibition of these platelet activation parameters in WT and C5-deficient plasma ( Figure 2D-F and supplemental Figure 2C), indicating that C5 activation is not connected to PDI roles in platelet activation. Importantly, PACMA31 added to C3 2/2 plasma also further suppressed convulxin-induced VWF binding, integrin a IIb b 3 activation, and P-selectin exposure, but showed no significant additive inhibition of the reduced platelet surface PS exposure seen in C3 2/2 mice (Figure 2A-C and supplemental Figure 2A).…”
Section: C5 Specifically Contributes To Fibrin Formation In Venous Thmentioning
confidence: 83%
“…24,28,29 Genetic evidence furthermore shows that the second catalytic domain of PDI is crucial for platelet activation that also involves Erp57, another platelet-expressed thiol isomerase. 30,31 Whether complement regulates platelet activation partially through thiol-disulfide exchange is currently unclear. Here we show that platelet activation and TF-dependent fibrin formation involve different stages of complement activation.…”
Section: Introductionmentioning
confidence: 99%
“…The FeCl 3 -induced model is one of the most widely used thrombosis models, which can not only provide valuable information about genetic modifications on platelet function and thrombosis 7,8,16,19,3133 , but can also be a valuable tool for evaluation of therapeutic compounds and strategies for treatment and prevention of atherothrombotic diseases 11,17,3437 . Here we have shown our modifications and refinements of this model and showed additional evidence of the utility of this technique, which is sufficiently sensitive to determine the effects of anticoagulant (tPA) and anti-platelet drugs (PAR4 antibody).…”
Section: Discussionmentioning
confidence: 99%
“…Several animal models have demonstrated that extracellular PDI has a critical role in thrombus formation (1,2). Inhibition of PDI by either monoclonal antibodies or small-molecule inhibitors prevents both platelet accumulation and fibrin formation at sites of vessel injury (2)(3)(4). Thrombus formation is also impaired in mice deficient in platelet PDI (5).…”
Section: Introductionmentioning
confidence: 99%